1970
DOI: 10.1111/j.2044-8279.1970.tb02114.x
|View full text |Cite
|
Sign up to set email alerts
|

Success and Failure Among Social Scientists and Health Scientists at a Technological University

Abstract: Summary. 186 students, 93 per cent of one intake of social and health scientists into the University of Bradford, were classified according to degree result and compared on a number of measures. Performance was found to be positively related to A‐level results and inversely to social class background, students from working‐class backgrounds being more likely to obtain good degrees. Introversion and open‐mindedness appeared to be an advantage in the social sciences, neuroticism in the health sciences. In both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…In the engineering and science schools no significant relationship was evident, but in modem languages a strong positive relationship was found. The findings of Smithers and Batcock (1970) with social and health scientists provided some support for the notion of an inverse relationship between performance and ease of access (Dale, 1963). But among the linguists of the present study a very different pattern was found.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In the engineering and science schools no significant relationship was evident, but in modem languages a strong positive relationship was found. The findings of Smithers and Batcock (1970) with social and health scientists provided some support for the notion of an inverse relationship between performance and ease of access (Dale, 1963). But among the linguists of the present study a very different pattern was found.…”
Section: Discussionsupporting
confidence: 55%
“…IN a previous paper (Smithers and Batcock, 1970) the bearing of a number of factors on the degree performance of health-science and social-science students at the University of Bradford was examined. In both fields of study working class students tended to be the more successful, and since both admitted about twice as many middle as working class students, this was taken as some support for Dale's (1963) hypothesis that, where it is difficult for a working class student to gain entry to a course, performance will be related inversely to social class.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commitment to teaching is closely related to subsequent employment; for instance, Cook (1987) reported that high commitment was strongly predictive of job status among PGCE students nine months after the end of their course. Similarly, 'strength of occupational motivation' is a significant predictor of success in a professionally oriented undergraduate course (Smithers & Batcock, 1970). More generally, commitment has been found to be an important determinant of job-related decisions, including intention to quit, and actual turnover (Clegg, 1983;Williams & Hazer, 1986).…”
Section: Academic Backgroundmentioning
confidence: 99%
“…Finally Smithers and Batcock also found the stable introvert to be better at social science (but not at health science!) [17], but Kline and Gale found social scientists spread right across the personality spectrum [18].…”
Section: Introductionmentioning
confidence: 99%